2007
DOI: 10.1530/rep-06-0130
|View full text |Cite
|
Sign up to set email alerts
|

Akt and Erk signal transduction pathways are early markers of differentiation in dominant and subordinate ovarian follicles in cattle

Abstract: Dominant follicles are those that continue to develop and have the potential to ovulate while subordinate follicles regress. Characteristics of dominant follicles include a larger diameter, higher intrafollicular estradiol, and lower IGF-binding protein (IGFBP)-4 concentrations compared with other cohort follicles. Follicle development is regulated by endocrine hormones that act via intracellular signaling pathways. Here, we show the differences in Akt, Erk, c-Jun N-terminal protein kinase, and p-38 signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…It has also been demonstrated in rodent follicle that the activation of LH and FSH is induced by other signaling pathways, including the AKT pathway (Carvalho et al 2003). Moreover, AKT is predominant in cattle and sheep dominant follicle compared to the subordinates and acts on progesterone secretion (Evans & Martin 2000, Ryan et al 2007. The correlation of the molecules involved in the network with different studies on folliculogenesis increases the confidence in our microarray results.…”
Section: Discussionsupporting
confidence: 72%
“…It has also been demonstrated in rodent follicle that the activation of LH and FSH is induced by other signaling pathways, including the AKT pathway (Carvalho et al 2003). Moreover, AKT is predominant in cattle and sheep dominant follicle compared to the subordinates and acts on progesterone secretion (Evans & Martin 2000, Ryan et al 2007. The correlation of the molecules involved in the network with different studies on folliculogenesis increases the confidence in our microarray results.…”
Section: Discussionsupporting
confidence: 72%
“…Ryan et al (2007) recently reported that both pathways, which are important for dominant follicle selection, show several differences in their expression profile in cattle follicles. However, few reports have investigated differences between the AKT and ERK pathways in expression, effects, and regulation in granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with subordinate follicles, dominant follicles have elevated follicular fluid E 2 concentrations (Fortune et al 2001, Ouellette et al 2005, Ryan et al 2007, Sisco & Pfeffer 2007) and synthetic capacity (Fortune et al 2001, Rhodes et al 2001, and increased free insulin-like growth factor 1 and decreased IGFBP4 and -5 (Beg & Ginther 2006). The dominant follicle in a first wave of the cycle is also slightly larger than one in a second wave (Manikkam et al 2001), and these have higher follicular fluid E 2 concentrations (Wolfenson et al 1999).…”
Section: Dominant and Subordinate Folliclesmentioning
confidence: 99%